REVITALISASI UMKM DESA BERBASIS DIGITAL - Anisa Kusumawardani; Maulana Ihsan Yusufi Suyatno; Rahmania Mustahidda; Kiswoyo; Ela Etik (CV. ALIM'SPUBLISHING, 2024)
The goals of this community service are to develop Gentansari Village MSMEs with their potential through marketing digitalization training, financial recording, education regarding capital and product design for e-commerce. Followed by approximately 40 MSME actors in Gentansari Village who produce various kinds of snacks. Carried out in two stages, the first stage is training regarding product design, financial recording, capital and social media management. The output of this activity is: increasing the knowledge and interest of MSME actors in Gentansari Village; creating a simple financial recording account; product design; management and commerce.